Teaching vocabulary to improve reading comprehension - Nagy, William E. (Urbana, Ill. : ERIC Clearinghouse on Reading and Communication Skills, 1988)
Explains how teachers can use vocabulary instruction to improve the reading comprehension of their students.
Includes bibliographical references (p. 40-42).
Professional
Keywords: Reading comprehension -- Study and teaching (Elementary) -- United States; Vocabulary -- Study and teaching (Elementary) -- United States; Reading comprehension -- Study and teaching; Vocabulary -- Study and teaching